Further Notes on Pseudogastropods - James X. Corgan (Hello World!, 1974)
Recently La Rocque (1973) discussed pseudogastropods: organisms that have been misidentified as gastropods and gastropods that have been incorrectly assigned to various phyla. His examples call attention to actual problems faced by those who deal with nomenclature. It seems desirable to record briefly two extreme cases: a fish that masqueraded as a gastropod (Hanna, 1925) and a group of gastropods that moved several giant steps downward in the Linnaean hierarchy and were interpreted as protozoans (Browne, 1971 ).